Fitting of Lotka-Volterra Model for Coupled Population Growth Data Through Least-Squares Estimation of Parameters - (:unkn) unknown (My University, 2020)
The population of two types of bacteria found in the Gulf Coast of Florida, V.chagasii and V. harveyi, can be described by the Lotka-Voltera competition model. Using data gathered in experiments conducted by Bury and Pickett (2015), we take a different approach to find parameter estimates using numerical methods in R. In particular, we find a numerical solution to the coupled set of ODEs and minimize the sum of squared errors in order to obtain the optimal parameter estimates that will fit the data best. In order to get a sense of accuracy of these parameter estimates, we use bootstrap estimation to compute the component wise standard deviations and construct confidence intervals for the estimates.
Keywords: least-squares; Lotka-Volterra; parameter estimation